Juridical Review of Inconsistency in The Implementation of Nafkah Iddah in Religious Court Rulings - Pratiwi, Widya; Tjoneng, Arman (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
In divorce cases involving talak ba'in sughra, providing iddah maintenance for ex-wives is still a controversial issue in legal practice. SEMA Number 2 of 2019 emphasizes that even if a wife is divorced through talak ba'in, she is entitled to iddah maintenance by prioritizing humanitarian considerations. However, irregularities arose due to differences in interpretation among judges, some of whom adhered firmly to Article 149 letter B and Article 119 of the Compilation of Islamic Law, which stipulates that a divorced wife is not entitled to iddah maintenance. This inconsistency results in wives' rights not being enforced evenly, thus compromising justice. This research uses normative juridical methods to analyze the application of law and legal interpretation regarding maintaining iddah. This underlines the critical role of the judge in determining the extent of the wife's right to iddah maintenance after divorce. To reduce this gap, there is an urgent need for the Supreme Court and high courts to align their interpretations. Achieving consensus regarding the implementation of SEMA Number 2 of 2019 across all judicial bodies will ensure consistent and fair treatment of wives who earn iddah income, align legal practices with humanitarian principles, and safeguard women's rights in the divorce process.